Biocompatible lipid nanocarriers for improved skin delivery of fluocinolone acetonide: physicochemical and in vitro performances - Stanković, Tijana; Ilić, Tanja; Dobričić, Vladimir; Tošić, Andjela; Pantelić, Ivana; Savić, Snežana (Archives of Pharmacy, 2023)
In order to improve the delivery of topical corticosteroids into inflammatory skin lesions while reducing the likelihood of adverse effects, lipid nanocarriers have received increasing attention. Hence, this study aimed to develop biocompatible nanoemulsions (NEs) and nanostructured lipid carriers (NLCs) as carriers for fluocinolone acetonide (FA) by carefully optimizing the formulation and process parameters. After an analysis of the relevant physicochemical parameters and stability testing, in vitro release and permeation tests were performed to evaluate whether the nanocarriers affected the penetration of FA into/through the skin compared to a conventional reference product (Sinoderm® cream). The developed NEs exhibited satisfactory physicochemical properties (droplet size <200 nm, PDI<0.2, ZP>ǀ-30ǀ mV, pH 4.75) and long-term stability. Although the developed NLCs initially had satisfactory properties, gelation was observed within 3 months of storage, implying that further formulation testing is required to resolve the limited stability of these systems. In vitro release/permeation findings suggest that the developed nanocarriers (especially NEs) provide better delivery of FA into/though the skin compared to the Sinoderm® cream. Therefore, a lecithin-based NE with a 10% lipid phase (medium-chain triglycerides/oleic acid 3:1) is a promising strategy for improved delivery of FA to the inflamed skin, allowing for ease of application, especially to larger skin surfaces and hairy regions.